Adolescent Migrants In The North Border Of Mexico: A Psychological Perspective - Marisela Gutiérrez Vega; Oscar Armando Esparza Del Villar; Priscila Montañez Alvarado; Irene Concepción Carrillo Saucedo (European Scientific Journal, ESJ, 2016)
The goal of this work was to show the psychological perspective of 84 adolescent migrants who were caught by American authorities during the time period of July 2014 and January 2015. Adolescents answered the Child Manifest Anxiety Scale (CMAS-R) and a semi-structured interview. Depending on their place of origin, anxiety could be affecting some more than others. It is highly recommended continuing this line of research since there are very few studies on the psychological perspective of Mexican and Central-American migrants who try to cross to the United States. Having a broader idea of this matter could generate interventions that will benefit this vulnerable group.